Analisis tingkat kesehatan Bank melalui Rasio Solvabilitas (Capital Adequacy Ratio): Studi kasus pada Bank BJB Syariah periode 2020-2024 - Faizah, Nilna Alfa; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2026)
Solvency is a fundamental indicator in assessing the resilience of Islamic banks against the risk of loss. This study aims to analyze the solvency performance of Bank BJB Syariah for the 2020-2024 period through a financial ratio approach, specifically the Capital Adequacy Ratio (CAR). The research method used is quantitative descriptive by analyzing secondary data in the form of published annual financial reports. The analysis focuses on the trend of the capital to Risk-Weighted Assets (RWA) ratio over the last five years. The results indicate that Bank BJB Syariah’s solvency level experienced fluctuations but remained within the healthy category according to the Financial Services Authority (OJK) minimum standards. This suggests that the bank possesses sufficient capital to absorb potential risks and support financing expansion. This CAR stability reflects effective capital management in maintaining long-term business sustainability. This study provides a comprehensive overview of the financial health of an Islamic regional development bank for stakeholders.